Xanthogranulomatous Osteomyelitis of the Tibia - Solooki, Saeed (Ochsner J, 2019)
Background: Xanthogranulomatous osteomyelitis (XO) is a rare chronic inflammatory process that is histologically characterized by the presence of foamy macrophages, histiocytes, and plasma cells. Radiologic and gross examinations can mimic malignancy, so definitive diagnosis should be made by histopathologic evaluation. Case Report: A 15-year-old male presented with pain in the proximal right leg for 2 weeks prior to admission. The patient had a history of leg trauma 3 years prior that was responsive to as-needed analgesics. Laboratory data revealed increased erythrocyte sedimentation rate and C-reactive protein. X-ray of the right tibia showed a periosteal reaction and bulging of bone with a questionable destruction of the cortex. Magnetic resonance imaging demonstrated an expansile bony lesion in the proximal metaphysis of the tibia. Histopathologic examination showed the bone trabecula surrounded by chronic inflammatory cells and a fragment of dead bone surrounded by histiocytes, foamy macrophages, and plasma cells. The pathologist confirmed the diagnosis of XO. Wound culture proved moderate growth of Staphylococcus aureus, and treatment with cefazolin and cephalexin was successful. Conclusion: The patient was not treated with the routine therapy used in previously reported cases (curettage), suggesting that antibiotic therapy should be considered before employing surgical interventions for XO.